2017
DOI: 10.1186/s12906-017-1821-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of lumbar spine stiffness and flexion-relaxation phenomenon with patient-reported outcomes in adults with chronic low back pain – a single-arm clinical trial investigating the effects of thrust spinal manipulation

Abstract: BackgroundSpinal manipulation (SM) is used commonly for treating low back pain (LBP). Spinal stiffness is routinely assessed by clinicians performing SM. Flexion-relaxation ratio (FRR) was shown to distinguish between LBP and healthy populations. The primary objective of this study was to examine the association of these two physiological variables with patient-reported pain intensity and disability in adults with chronic LBP (>12 weeks) receiving SM.MethodsA single-arm trial provided 12 sessions of side-lying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…Close to half of the articles stated less than 25% of all elements, showing a general low potential to be replicated. When observing which items were mostly reported, we can observe that Location was by far the one that almost all studies reported, only Bialoszewski et al, (2014) and Xia et al, (2017) did not.…”
Section: Discussionmentioning
confidence: 94%
“…Close to half of the articles stated less than 25% of all elements, showing a general low potential to be replicated. When observing which items were mostly reported, we can observe that Location was by far the one that almost all studies reported, only Bialoszewski et al, (2014) and Xia et al, (2017) did not.…”
Section: Discussionmentioning
confidence: 94%
“…This study demonstrated that patients with DLS enjoyed significant improvement in pain, physical function and deformity after long-level fusion, which was similar to previous studies. Patients with high levels of disability due to sagittal imbalance or spinal stenosis had been demonstrated to experience substantial benefit from total lumbar arthrodesis surgery as compared with nonoperative treatment with respect to reductions in leg and back pain and improvements in physical function [21,14,[22][23][24][25]. However, despited the benefits of correction surgery, extensive spinal fusion also resulted in limited flexibility and to some extent impaired ADL, especially for elderly patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Functional disability was assessed using the Rolland Morris Disability Questionnaire (RMQ). Results of RMQ was determined as a functional state if score ≤4, and dysfunctional state if score >4 (Xia et al, 2017).…”
Section: Methodsmentioning
confidence: 99%